A wintertime study of PM2.5-bound polycyclic aromatic hydrocarbons in Taiyuan during 2009–2013: Assessment of pollution control strategy in a typical basin region. (September 2016) - Li, Hongyan; Guo, Lili; Cao, Runfang; Gao, Bo; Yan, Yulong; He, Qiusheng
Abstract: Taiyuan city in Shanxi province, China has been one of the top heavily polluted cities in the world for a long time with large industrial emissions and high disease burden. Many pollution control strategies have been implemented forcefully by the government in recent years in Taiyuan. To better understand the effect of the strategies and related influence factors, we studied polycyclic aromatic hydrocarbons (PAHs) in fine particulate matter (PM2.5 ) during heating seasons in Taiyuan from 2009 to 2013. The results showed that the concentrations of PM2.5 (70.7–477.9 μg/m 3 ) and related total PAHs (T-PAHs, 128.7–1840.2 ng/m 3 ) far exceeded the air quality standards issued by the Ministry of Environmental Protection of China (MEP) and were higher than those in many domestic and foreign cities in spite of the pollution control. Source apportionment by the diagnostic ratio analysis and PMF model found that coal consumption contributed the most (52.1%) to the total PM2.5 -bound PAHs followed by the coking industry (27.3%) and traffic exhausts (20.6%). Significant decreases in PM2.5 and PAHs levels were found in 2013, which was probably due to the large abatement of residential coal consumption and favorable meteorological factors. Being located in the north of Taiyuan basin, the pollution in Taiyuan could be aggravated by the regional transport of coal combustion- and coking-related pollutants from other industrial development zones in the south-western basin as found by the analysis of meteorological influence and back trajectory. Although the PAHs were the lowest in 2013, the BaPeq or ILCR were the highest in that year. This should be related to the increasing vehicle numbers in Taiyuan, because vehicle exhaust tends to enrich in higher molecular weight and more toxic PAHs. Our results provided useful guidance for solving the air pollution problem for cities in a semi- or total-closed basin with coal as the major energy source such as Taiyuan. Highlights: PM2.5 -bound PAH pollution in Taiyuan was still serious despite being controlled. Coal combustion and coking activities dominated the sources of PAHs in PM2.5 . Coal/coking-related PAHs emitted in Taiyuan basin could be transported to Taiyuan. Increasing local traffic caused increasing health risk through enriching HMW PAHs. Controlling residential coal combustion was effective to abate PAHs pollution.